Association of interleukin 13 gene polymorphisms and plasma IL 13 level with risk of systemic lupus erythematosus. (April 2018) - Wang, Rong; Lu, Yu-Lan; Huang, Hua-Tuo; Qin, Hai-Mei; Lan, Yan; Wang, Jun-Li; Wang, Chun-Fang; Wei, Ye-Sheng
Highlights: rs20541 CT/TT genotypes are a risk factor for SLE, probably by increasing the level of IL-13. T allele in rs20541 was associated with increased risk of SLE. The concentration of IL-13 in SLE was significantly higher than the controls. CT and TT genotypes in rs20541 were associated with increased risks of renal disorder in SLE. Abstract: Interleukin (IL) 13 plays a critical role in inflammatory diseases, including systemic lupus erythematosus (SLE). This study aims to explore the potential association of IL-13 polymorphisms with the risk of SLE. We genotyped IL-13 rs20541, rs848 and rs1295686 using Snapshot SNP genotyping assays. Plasma IL-13 level was determined by enzyme-linked immunosorbent assay (ELISA). We found that rs20541 was associated with increased risk of SLE (CT vs. CC: adjusted OR = 1.43, 95%CI, 1.04–1.99, P = .030; TT vs. CC: adjusted OR = 1.73, 95%CI, 1.10–2.73, P = .018; CT/TT vs. CC: adjusted OR = 1.50, 95%CI, 1.10–2.04, P = .010; T vs. C adjusted OR = 1.34, 95%CI, 1.08–1.93, P = .031). CT and TT genotypes in rs20541 were associated with increased risk of renal disorder in SLE (CT vs. CC: adjusted OR = 1.97, 95%CI, 1.18–3.28, P = .009; TT vs. CC: adjusted OR=2.42, 95%CI, 1.22–4.77, P = .011). Moreover, The concentration of IL-13 was significantly elevated in rs20541 CT/TT genotypes compared with CC genotype ( P < .001). These results suggest that rs20541 CT/TT genotypes may be a risk factor for SLE, probably by increasing the level of IL-13.